PERANCANGAN PROTOTYPE ALAT BAJAK SAWAH DENGAN PENGONTROLAN MENGGUNAKAN BLUETOOTH BERBASIS ANDROID - Arief Cahya Purnomo (LPPM Universitas Abdurrab, 2020)
Indonesia is a country that has extensive paddy fields, these lands are plowed manually or traditionally, manually plowing the fields by plowing the fields by pushing the plows around the land and the traditional way of plowing the fields using cattle. In the current era of technology, it is needed a field plow that can be controlled remotely. The purpose of the authors designed this tool so that it can simplify the work of farmers and change the system of plowing rice fields from manual to modern. There are two important parts of the design of this tool namely the design of hardware (hardware) in the form of a prototype of a rice plow tool and the design of software (software) in the form of a control program. The design of the control of the rice plow consists of several components, including: android application as a control device, bluetooth HC-05 as a communication medium to Arduino Nano, Arduino Nano as a microcontroller that gives commands to the L298N Driver to drive a DC motor. This test is carried out 3 times by activating and deactivating the power supply. The results obtained from this test are 100% successful without any errors / damage.